TSH Elevations as the First Laboratory Evidence for Pseudohypoparathyroidism Type Ib (PHP‐Ib). (May 2015) - Molinaro, Angelo; Tiosano, Dov; Takatani, Rieko; Chrysis, Dionisios; Russell, William; Koscielniak, Nikolas; Kottler, Marie‐Laure; Agretti, Patrizia; De Marco, Giuseppina; Ahtiainen, Petteri; Christov, Marta; Mäkitie, Outi; et al.
ABSTRACT Hypocalcemia and hyperphosphatemia because of resistance toward parathyroid hormone (PTH) in the proximal renal tubules are the most prominent abnormalities in patients affected by pseudohypoparathyroidism type Ib (PHP‐Ib). In this rare disorder, which is caused by GNAS methylation changes, resistance can occur toward other hormones, such as thyroid‐stimulating hormone (TSH), that mediate their actions through G protein‐coupled receptors. However, these additional laboratory abnormalities are usually not recognized until PTH‐resistant hypocalcemia becomes clinically apparent. We now describe four pediatric patients, first diagnosed with subclinical or overt hypothyroidism between the ages of 0.2 and 15 years, who developed overt PTH‐resistance 3 to 20 years later. Although anti‐thyroperoxidase (anti‐TPO) antibodies provided a plausible explanation for hypothyroidism in one of these patients, this and two other patients revealed broad epigenetic GNAS abnormalities, which included loss of methylation (LOM) at exons AS, XL, and A/B, and gain of methylation at exon NESP55; ie, findings consistent with PHP‐Ib. LOM at GNAS exon A/B alone led in the fourth patient to the identification of a maternally inherited 3‐kb STX16 deletion, a well‐established cause of autosomal dominant PHP‐Ib. Although GNAS methylation changes were not detected in additional pediatric and adult patients with subclinical hypothyroidism (23 pediatric and 39 adult cases), hypothyroidism can obviously be the initial finding in PHP‐Ib patients. One should therefore consider measuring PTH, along with calcium and phosphate, in patients with unexplained hypothyroidism for extended periods of time to avoid hypocalcemia and associated clinical complications. © 2014 American Society for Bone and Mineral Research © 2014 American Society for Bone and Mineral Research.